2021
DOI: 10.1021/acsami.0c22987
|View full text |Cite
|
Sign up to set email alerts
|

Tunable NH4F-Assisted Synthesis of 3D Porous In2O3 Microcubes for Outstanding NO2 Gas-Sensing Performance: Fast Equilibrium at High Temperature and Resistant to Humidity at Room Temperature

Abstract: NO2 gas sensors based on metal oxides under wild conditions are highly demanded yet an incomplete surface reaction and humidity interference on the gas-sensing performance limit their applications. Herein, we report three-dimensional (3D) porous In2O3 microcubes via a simple hydrothermal strategy to produce outstanding NO2 gas-sensing performance: fast equilibrium of the surface reaction at 150 °C and negligible humidity dependence on the NO2 gas sensing at room temperature. The 3D porous In2O3 microcubes with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 58 publications
(27 citation statements)
references
References 43 publications
1
26
0
Order By: Relevance
“…Once introduced, it will rapidly seize the free electrons on the surface of the NWs. This process consumes the electrons of the In 2 O 3 NWs and further increases the resistance of the NWs, expressed as eqs and . , When these NO 2 gases are evacuated, NO 2 – will return electrons to the oxygen vacancy in eqs and , and the device will return to its initial state. Figure displays the NO 2 response mechanism.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Once introduced, it will rapidly seize the free electrons on the surface of the NWs. This process consumes the electrons of the In 2 O 3 NWs and further increases the resistance of the NWs, expressed as eqs and . , When these NO 2 gases are evacuated, NO 2 – will return electrons to the oxygen vacancy in eqs and , and the device will return to its initial state. Figure displays the NO 2 response mechanism.…”
Section: Resultsmentioning
confidence: 99%
“…In the meanwhile, the Au catalyst is believed to be complementary metal oxide semiconductor (CMOS) technology incompatible, necessitating alternative metal catalysts. In addition, In 2 O 3 nanostructures have also been reported with other methods to test NO 2 . For example, Liu et al used porous In 2 O 3 to improve NO 2 detection by the hydrothermal method . Zhang et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ammonium fluoride (NH 4 F), which is a versatile inorganic salt, has attracted significant research interest for morphology control [1][2][3] and transition-metal anion doping [4] in the catalysis and energy fields. As a popular morphology-directing agent, previous studies have revealed that the fluorine ion (F − ), which is released from NH 4 F in the growth solution, provides numerous active sites for the nucleation and growth of nanostructures to control morphology evolution.…”
Section: Introductionmentioning
confidence: 99%
“…The thickness of the Co­(OH)F layer dramatically decreases with the increase of NH 4 F concentration (Figure i,l,o). The changes of morphology and thickness are mainly due to the corrosion of F – and the strongly acidic condition from the excess addition of NH 4 F, which dramatically restrain the hydrolysis of urea and the following crystal growth. , Correspondingly, the EDS results also manifest that the content of fluorine element in the precursors increases with the added concentration of NH 4 F, further indicating the key factor of F – in the phase formation and morphological changes (Table S1). Afterward, the obtained cobalt carbonate hydrate and Co­(OH)F precursors with different morphologies are subsequently converted into CoP nanostructures using NaH 2 PO 2 as the phosphorus source at 350 °C for 2 h in a tubular furnace under the protection of pure Ar.…”
Section: Resultsmentioning
confidence: 88%